Dietary Bile Acids Enhance Growth, and Alleviate Hepatic Fibrosis Induced by a High Starch Diet via AKT/FOXO1 and cAMP/AMPK/SREBP1 Pathway in Micropterus salmoides - Yu, Huanhuan; Zhang, Lulu; Chen, Pei; Liang, Xiaofang; Cao, Aizhi; Han, Juan; Wu, Xiufeng; Zheng, Yinhua; Qin, Yuchang; Xue, Min (Frontiers in Physiology, 2019)
A 10-week feeding trial was conducted to investigate the effects of dietary bile acids (BA) on growth, glucose and lipid metabolism, liver histopathology and the underlying regulation mechanism on AKT/FOXO1 and cAMP/AMPK/SREBP1 pathway in largemouth bass (Micropterus salmoides) fed with a high starch diet. Six experimental diets were prepared with BA levels at 0 (B0), 80 (B80), 160 (B160), 240 (B240), 300 (B300) and 600 (B600) mg/kg in a basal diet with 18.7% starch. Each diet was fed to 6 replicates with 30 fish (6.17 ± 0.03 g) in each tank. The highest weight gain rate was observed in B300 group and the optimal level of BA was estimated at 475 mg/kg by a monistic cubic equation regression analysis. Dietary BA inclusion decreased hepatosomatic index and hepatic lipid content significantly. The fish in B300 group clearly showed alleviated hepatic fibrosis, but more steatohepatitis symptoms diagnosed with various histopathological and immunofluorescence analysis. 10 out of 12 samples were observed hepatic fibrosis in B0 group while only 2 fibrosis samples in B300 group. The promoted liver histopathology by dietary BA was related to improved glucose and lipid metabolism. Dietary BA inhibited the expression of G6Pase by activating AKT and reducing FOXO1 transcription, which improved the regulation ability of gluconeogenesis, activated cAMP/AMPK and repressed SREBP1 transcription to inhibit hepatic lipogenesis, which prevented hepatic lipid accumulation. In conclusion, dietary BA enhanced the growth and alleviated liver fibrosis induced by a high starch diet to steatohepatitis/recovery symptom via improving glucose and lipid metabolism, which regulated by AKT/FOXO1 and cAMP/AMPK/SREBP1 pathway in largemouth bass.